(untitled) (Research, Society and Development, 2020)
This work aims to analyze the perception of students in the 2nd year of the IFMG Industrial Automation Integrated Technician course regarding the use of eduScrum as a teaching methodology. EduScrum is the application in education of the Scrum framework. At eduScrum, the teacher presents students with why to study and what will be studied and delivered, students will decide how they will learn and develop the proposed activity. This methodology has several stages, such as: Team building, Sprint planning, Sprint development, Stand up meetings, Sprint review and Sprint retrospective. All of these steps are based on the principles of transparency, adaptation and inspection. This study was developed from a pedagogical intervention, and for the stage of investigating perceptions, field research was used. EduScrum was used during the first quarter of 2018 in the discipline of Industrial Manufacturing, CNC and Hydropneumatic Systems. After the end of the quarter, the 43 students answered a questionnaire on Google Forms. The use of this methodology was very satisfactory, and 90.7% of students would like it to be used in the next quarter. The main points favorable to the use of eduScrum presented by the students were: the favor of learning, the development of group work, responsibility and autonomy.